THE EURO-ATLANTIC SECURITY AND THE TERRORISM - Dinca, Marian; Dinca, Alexandru-Marian (International Journal of Legal and Social Order, 2021)
The security of Euro-Atlantic area must be analyzed and understood in the context of the international security environment specific to the beginning of the 21st century, an active and effervescent one, where hybrid threats and deep economic and social imbalances are real risks. The terrorism has been, is and will continue to be a topic of maximum interest. The approach of this phenomenon from the psychological perspective not only of those directly involved, but also of those affected after the attack, is of interest and very topical, in the context of the unprecedented technological and informational explosion.